Sustainable Development, Interdisciplinarity and Environmental Sciences - Junior, Arlindo Philippi; Sobral, Maria do Carmo; Fernandes, Valdir; Sampaio, Carlos Cioce (Revista Brasileira de Pós-Graduação, 2014)
This article addresses the debate on interdisciplinarity in research as well as in postgraduate studies in Brazil, with a focus on Environmental Sciences. It aims at presenting a discussion about the institutionalization of interdisciplinarity and of postgraduate studies in Environmental Sciences in Brazilian postgraduate studies, based on the experience of the authors, documental analyses and bibliography evaluation. In light of the data about the evolution of postgraduate education in Brazil, institutionalization is presented, and the interdisciplinary practice is discussed in postgraduate research in Environmental Sciences, highlighting pathways and challenges for the near future.